Answer: 5
Step-by-step explanation: d = √(x^²-x^₁)^2+(y^²-y^₁)^2 d = √ (-9--5)^2+ (-2 - -5)^2 d = √(-4)^2 + (3)^2 d = √16 + 9 d = √25 d = 5
Answer:
1,687,500,000,000
Step-by-step explanation:
1) 270,000,000 x 6250
First find out how much money she spent by doing 80 (original amount) - 33.56 (amount after spending): $46.44
Now she spent 46.44 dollars and each pound is 7.74:
46.44 / 7.74 = 6
She bought 6 lbs
Answer:
(1, 10)
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
<u>Algebra I</u>
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define Systems</u>
-5x + 6y = 55
4x + 3y = 34
<u>Step 2: Rewrite Systems</u>
4x + 3y = 34
- Multiply everything by -2: -8x - 6y = -68
<u>Step 3: Redefine Systems</u>
-5x + 6y = 55
-8x - 6y = -68
<u>Step 4: Solve for </u><em><u>x</u></em>
<em>Elimination</em>
- Combine equations: -13x = -13
- Divide -13 on both sides: x = 1
<u>Step 5: Solve for </u><em><u>y</u></em>
- Define equation: 4x + 3y = 34
- Substitute in <em>x</em>: 4(1) + 3y = 34
- Multiply: 4 + 3y = 34
- Isolate <em>y</em> term: 3y = 30
- Isolate <em>y</em>: y = 10
Answer:
final cost of 3 pounds: <u> 8 dollars </u>
final cost of p pounds: <u> 3.75p - 3.25 dollars </u>
Step-by-step explanation:
Each pound costs $3.75, so 3 pounds cost 3*3.75 = 11.25 dollars. Subtract off the $3.25 to get the final cost to be 11.25-3.25 = 8 dollars. This takes care of the first part.
For the second part, the expression for the final cost is 3.75p - 3.25; where the 3.75p is the cost before the coupon is applied. If you plugged p = 3 into that expression, you should get 8 as a result. The variable p is some positive whole number. It's a place holder for the number of pounds of apples.